Literary and Aesthetic Features of Historiography in Uzbek Women’s Poetry (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the literary and aesthetic features of historiography in Uzbek women’s poetry, focusing on key works such as Dilshodi Barno’s Tarixi muhojiron and Gulbadanbegim’s Humoyunoma. While Uzbek literary studies have long emphasized male-centered historical narratives and national identity, there remains a notable knowledge gap regarding the unique ways women poets construct historical meaning through artistic forms. To address this, the study employs a qualitative literary analysis grounded in M.M. Bakhtin’s chronotope theory and feminist literary criticism, conducting close readings of selected texts alongside comparative insights drawn from broader Uzbek and English literary traditions. The findings reveal that women poets embed historical consciousness within emotional, domestic, and spiritual frameworks, using metaphor, symbolism, and lyrical voice to present nuanced perspectives on exile, loyalty, moral endurance, and cultural memory. Results show that these works not only challenge dominant historiographical conventions but also contribute to a richer, gender-inclusive understanding of Uzbekistan’s literary heritage. The study’s implications extend to both literary theory and cultural history, underscoring the importance of recognizing female voices as historiographical agents and advocating for their integration into national literary canons. Further research is recommended to explore comparative cross-cultural patterns, conduct archival investigations, and apply digital humanities tools to trace larger networks of women’s historical writing in Central Asia, ultimately deepening theoretical and practical engagement with the intersection of gender, literature, and historiography.